Research on International Comparison and Reference in Vocational Education - SONG Jinxi (Journal of Exploration of Vocational Education, 2025)
Abstract：Vocational education plays a significant role in promoting economic transformation and enhancing the adaptability of the labor market. However, its policy design and implementation effects vary significantly across different countries. This study conducts a comparative analysis of Germany’s "dual system," the market-driven vocational education model in the United Kingdom, and Australia’s international development experience. It explores the commonalities and differences in key areas such as the integration of industry and education, quality assurance, and international development, and analyzes the implications for optimizing vocational education in China. The research finds that common trends in vocational education across these countries include: the deep integration of vocational education with economic transformation, further strengthening of industry-education collaboration, and continuous improvement of policy support. Germany’s "dual system" has achieved an organic combination of theory and practice through legally guaranteed school-enterprise cooperation; the UK’s market-driven model demonstrates high flexibility but lacks depth in corporate involvement; while Australia has enhanced the global competitiveness of its vocational education through international cooperation and a quality certification system. Furthermore, the study reveals challenges faced by vocational education’s internationalization in areas such as local adaptation, resource allocation, and rapid expansion. This study suggests that China should deepen school-enterprise cooperation through legal guarantees, establish a unified quality certification system, and leverage the "Belt and Road" initiative to promote international development. Additionally, strengthening multi-country collaboration and policy learning is essential to explore a vocational education model that is both universal and flexible. The study provides theoretical support for international comparisons of vocational education and offers practical recommendations for the reform and globalization of vocational education in China.